EDUKASI DAN PENDAMPINGAN KEWIRAUSAHAAN BIDANG PEREKONOMIAN UMKM PETERNAKAN AYAM PETELUR DI DESA SUKAWANA - Ni Ketut Muliati; I Made Endra Lesmana Putra; Ni Putu Trisna Windika Pratiwi; I Gede Aryana Mahayasa (UNHI Press, 2023)
Laying hens farming is a business option that the community in Sukawana Village can work on. Laying hen farming business has a strategic value, especially in the provision of animal protein to meet the needs of the community, in addition to its role in taking advantage of employment opportunities. Community service activities are carried out at Kobar Farm which is located at Sukawana Kintamani Bangli Village. Starting with an initial survey to determine target partners to providing education and training related to aspects of marketing and brand awareness, business capital through credit analysis and recording and bookkeeping related to production and sales. The existence of this service activity was welcomed by the service partners and hoped that there would be ongoing coaching. We as a service team hope that the contributions we provide can be of benefit to partners in developing their business.